X-men first class [videorecording (Blu-Ray)] - Singer, Bryan, 1965-; Vaughn, Matthew, 1971-; McAvoy, James, 1979-; Fassbender, Michael, 1977-; Bacon, Kevin, 1958-; Byrne, Rose; Platt, Oliver; Jones, January, 1978- (Twentieth Century Fox Home Entertainment, 2011)
Before Charles Xavier and Erik Lensherr took the names Professor X and Magneto, they were two young men discovering their superhuman powers for the first time, working together in a desperate attempt to stop the Hellfire Club and a global nuclear war.